Functional and Structural Findings of Neurodegeneration in Early Stages of Diabetic Retinopathy: Cross-sectional Analyses of Baseline Data of the EUROCONDOR Project - B M Santos, Ana Rita (2017)
This cross-sectional study evaluated the relationship between 1) functional and structural measurements of neurodegeneration in the initial stages of diabetic retinopathy (DR) and 2) the presence of neurodegeneration and early microvascular impairment. We analyzed baseline data of 449 patients with type 2 diabetes enrolled in the European Consortium for the Early Treatment of Diabetic Retinopathy (EUROCONDOR) study (NCT01726075). Functional studies by multifocal electroretinography (mfERG) evaluated neurodysfunction, and structural measurements using spectral domain optical coherence tomography (SD-OCT) evaluated neurodegeneration. The mfERG P1 amplitude was more sensitive than the P1 implicit time and was lower in patients with Early Treatment of Diabetic Retinopathy Study (ETDRS) level 20-35 than in patients with ETDRS level <20 (P = 0.005). In 58% of patients, mfERG abnormalities were present in the absence of visible retinopathy. Correspondence between SD-OCT thinning and mfERG abnormalities was shown in 67% of the eyes with ETDRS <20 and in 83% of the eyes with ETDRS level 20-35. Notably, 32% of patients with ETDRS 20-35 presented no abnormalities in mfERG or SD-OCT. We conclude that there is a link between mfERG and SD-OCT measurements that increases with the presence of microvascular impairment. However, a significant proportion of patients in our particular study population (ETDRS ≤35) had normal ganglion cell-inner plexiform layer thickness and normal mfERG findings. We raise the hypothesis that neurodegeneration may play a role in the pathogenesis of DR in many but not in all patients with type 2 diabetes.